2022
DOI: 10.3390/microorganisms10050900
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Evolutionary Dynamics of Human Influenza Type-A Viruses in Africa: A Systematic Review

Abstract: Genomic characterization of circulating influenza type-A viruses (IAVs) directs the selection of appropriate vaccine formulations and early detection of potentially pandemic virus strains. However, longitudinal data on the genomic evolution and transmission of IAVs in Africa are scarce, limiting Africa’s benefits from potential influenza control strategies. We searched seven databases: African Journals Online, Embase, Global Health, Google Scholar, PubMed, Scopus, and Web of Science according to the PRISMA gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 144 publications
(524 reference statements)
0
11
0
Order By: Relevance
“…This is the first and largest study to sequence Uganda A(H1N1)pdm09 and A(H3N2) virus whole genomes (WGs) locally, and extensively describe the genetic diversity and evolution patterns of Africa IAVs since 1994. Our work expands on previous influenza sequencing and characterisation efforts of African researchers 10 and highlights the feasibility of next-generation whole-genome sequencing for real-time disease surveillance and detection of emerging strains in Africa. Our newly-generated sequences add significantly to public Africa IAV genomes.…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…This is the first and largest study to sequence Uganda A(H1N1)pdm09 and A(H3N2) virus whole genomes (WGs) locally, and extensively describe the genetic diversity and evolution patterns of Africa IAVs since 1994. Our work expands on previous influenza sequencing and characterisation efforts of African researchers 10 and highlights the feasibility of next-generation whole-genome sequencing for real-time disease surveillance and detection of emerging strains in Africa. Our newly-generated sequences add significantly to public Africa IAV genomes.…”
Section: Discussionmentioning
confidence: 64%
“…Based on our dataset, similar clades circulated in Uganda and other African countries, except for A(H1N1)pdm09 clade 7, HK, and H1-UG2 (Supplementary Table 7 ). However, our recent systematic review showed that clade 7-like strains also circulated in Kenya, Tanzania, and South Africa between 2010 and 2012 10 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations